As dinâmicas de transiç\~ao energética no Brasil e na Argentina: Potencialidades, limites e papel da China - Carlos Renato Ungaretti; Ticiana Gabrielle Amaral Nunes; Marco Aurélio Alves de Mendonça (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– In light of the debate on the distinction between addition and energy transition, this study sought to identify the potential and limitations of Chinese investments and financing for the decarbonization of the economies of Brazil and Argentina, as well as to verify the similarities and differences between the modes of operation of Chinese companies and institutions in each country. Both countries have seen the growth of Chinese engagement in the renewable energy sector in recent years. It was argued that China has been contributing to the energy diversification trajectories of both countries, with impacts, potential and limitations that are sometimes similar and sometimes different. It was noted that in Brazil, the acquisition of existing assets predominates, while in Argentina, financing plays a more relevant role. The reduction of energy intensity in the generation sector in Argentina was identified. The potential lies in the expansion of capacities through investments in new units and internalization of production chains associated with the energy transition. The prevalence of acquisitions in the Brazilian market is an important limitation, while the macroeconomic fragilities of Argentina present an important challenge.
Keywords: Q42; F21; F5; 330; Brazil; Argentina; China; Energy Transition; Investments